2014
DOI: 10.1089/ten.tea.2013.0400
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-GAG Scaffold Biophysical Properties Bias MSC Lineage Choice in the Presence of Mixed Soluble Signals

Abstract: Biomaterial strategies for regenerating multitissue structures require unique approaches. One strategy is to design scaffolds so that their local biophysical properties can enhance site-specific effects of an otherwise heterogeneous biomolecular environment. This investigation examined the role of biomaterial physical properties (relative density, mineral content) on the human mesenchymal stem cell phenotype in the presence of mixed soluble signals to drive osteogenesis or chondrogenesis. We tested a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Measures of metabolic activity give a good representation of the overall metabolic health of the cell-seeded biomaterials, 32, 34, 61 they are not exact measures of total cell number. Given previous studies favorably comparing explicit measures of cell number versus metabolic activity of cell-seeded CG scaffolds 62, 63 as well as the large number of scaffold groups and experimental end-points in this study, we chose not to explicitly determine cell number via destructive assays, but rather tracked construct metabolic activity via non-destructive AlamarBlue.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of metabolic activity give a good representation of the overall metabolic health of the cell-seeded biomaterials, 32, 34, 61 they are not exact measures of total cell number. Given previous studies favorably comparing explicit measures of cell number versus metabolic activity of cell-seeded CG scaffolds 62, 63 as well as the large number of scaffold groups and experimental end-points in this study, we chose not to explicitly determine cell number via destructive assays, but rather tracked construct metabolic activity via non-destructive AlamarBlue.…”
Section: Discussionmentioning
confidence: 99%
“…We showed anisotropic scaffolds containing structural alignment cues can enhance alignment, proliferation and transcriptomic stability of equine tenocytes, [15, 16] while also selectively activate mechanotransduction paths and MSC tenogenic differentiation in the absence of growth factors supplementation. [9, 17, 18] We have separately demonstrated a hydroxyapatite mineralized CG scaffold that enhanced MSC differentiation towards an osteogenic lineage, again in the absence of conventional osteogenic supplements. [18, 19] We have recently described a method to generate multi-compartment scaffolds that contain discrete scaffold regions connected by a continuous interface.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work with CG scaffolds has shown that the incorporation of soluble and covalent biomolecules into CG scaffolds impacts cellular behavior. 20, 26, 29, 53 However, these studies have focused on contributions of the total factor present without distinguishing the impacts of specific attachment and fouling individually. For this study we examined how the manipulation of treatment parameters for two covalent immobilization strategies impacted both covalent attachment and fouling.…”
Section: Discussionmentioning
confidence: 99%
“…However, like with many biomaterial platforms, it has become apparent that biomolecular signals added to culture media can enhance or help direct cellular responses. 2629 …”
Section: A Introductionmentioning
confidence: 99%